Altitude training in elite swimmers for sea level performance (altitude project) - Rodriguez, F. A.; Iglesias, X.; Feriche, B.; Calderon-Soto, C.; Chaverri, D.; Wachsmuth, N.; Schmidt, W.; Levine, B. D. (Medicine & Science in Sports & Exercise, 2015)
Introduction: This controlled, nonrandomized, parallel-groups trial investigated the effects on performance, VO2 and hemoglobin mass (tHbmass) of four preparatory in-season training interventions: living and training at moderate altitude for 3 and 4 wk (Hi-Hi3, Hi-Hi), living high and training high and low (Hi-HiLo, 4 wk), and living and training at sea level (SL) (Lo-Lo, 4 wk).